Variations in initial 26Al/27Al ratios among fine-grained Ca-Al-rich inclusions from reduced CV chondrites. (15th June 2020) - Kawasaki, Noriyuki; Wada, Sohei; Park, Changkun; Sakamoto, Naoya; Yurimoto, Hisayoshi
Abstract: Fine-grained Ca-Al-rich inclusions (FGIs) in CV chondrites are suggested to be condensates formed directly from the solar nebular gas. Al–Mg mineral isochrons of seven FGIs from reduced CV chondrites Efremovka, Vigarano, Thiel Mountains 07007, and Northwest Africa 8613 were obtained via in situ Al–Mg isotope measurements using secondary ion mass spectrometry. The slopes of the mineral isochrons for seven FGIs exhibit statistically significant variations in initial 26 Al/ 27 Al ratios, ( 26 Al/ 27 Al)0, ranging from (5.19 ± 0.17) to (3.35 ± 0.21) × 10 −5, which correspond to a relative age spread of 0.44 ± 0.07 Myr. Inferred upper limit of ( 26 Al/ 27 Al)0 for the FGIs is identical to the Solar System ( 26 Al/ 27 Al)0 of ∼5.2 × 10 −5 as determined by whole-rock Al–Mg isochron studies for CAIs in CV chondrites. The intercepts of the mineral isochrons, the initial 26 Mg/ 24 Mg ratios the FGIs formed with, are consistent with Mg-isotope evolution path of a solar-composition nebular gas. The observed variations in ( 26 Al/ 27 Al)0 for FGIs are essentially similar to those (∼5.2 to ∼4.2 × 10 −5 ) for coarse-grained, igneous CAIs of CV chondrites that are formed by melting and solidification. If 26 Al was distributed homogeneously in the forming region, then our data indicate that thermal processes of condensation and melting for CAI formation occurred contemporaneously and continued for at least ∼0.4 Myr at the very beginning of the Solar System. Alternatively, the observed variations in ( 26 Al/ 27 Al)0 also indicate the possibility of heterogeneous distributions of 26 Al in the forming region, corresponding to a range of over at least 3.4 × 10 –5  < ( 26 Al/ 27 Al)0  < 5.2 × 10 –5 .